The role of different opportunities in the activation and use of the business opportunity prototype - Costa, S. (2016)
This study analyses how the different nature of business opportunities affects the way potential entrepreneurs recognize a business opportunity prototypical features. Although scholars have examined the reasons why some individuals, but not others, identify business opportunities, little is known about how the nature of the business opportunity (i.e., its context) affects the recognition of the business opportunity characteristics. Moreover, most studies on opportunity identification rely either on retrospective data or on entrepreneurs' prior knowledge and experience. Thus, little is said about how cognitive structures are used by potential entrepreneurs upon opportunity recognition. Participants in this study (70 university students) were presented with one of two scenarios describing two different business opportunities - an independent entrepreneurial opportunity and a business reformulation opportunity - and were asked to describe the business opportunity in their own words. The analysis performed showed that there are significant differences in the way respondents recognized the prototypical characteristics of both business opportunities. Specifically, participants were more risk-averse in the business reformulation opportunity than in the entrepreneurial opportunity. In the latter case, the participants focused more on customers. No differences were found regarding the identification of prototypical characteristics referring to profit.